UTILIZAÇÃO DE MÉTODO DE AUXÍLIO MULTICRITÉRIO À DECISÃO NA ESCOLHA DE FORNECEDORES DE COMPONENTES ESTRATÉGICOS. - Moreira, William de Freitas (2006)
The companies of automotive segment have achieved a great transformation from the 90th years on. At the management, the japanese practices (lean production practices and just in time, between others), quality and enviroment system management, healthy and safety supply chain management, corporate governance, internet and new technologies, shall be pointed as main factors of this transformation. In this cenary, the purchasing area has started to develop a strategic role. It was envolved in a complex process that is the new products development close to engineering, marketing and finances for instance. This way, the purchasing area as the door through which goes out the company s money, was risen to the condition of company s supply chain manager. The selection of a component supplier pass through some new concepts: either imported or local content, supply mode, verticalization and modular production, beyond the already known, price, quality and on time delivery. More, the corporate governance requires strongly an ethic conduction of all supplier selection process. From the bibliography avaiable and researched on, and following construction of a Theorical Concept Set, it has been verified that the Multicriteria Decision Aid method is a new tool to be used by buyers in the strategic components s supplier selection process. The target to be approached in this work will be the use of a Multicriteria Decision Aid method, in this case the ELECTRE TRI, in order to sellect and nominate a supplier of strategical components to assembly a car.